PLGA nanoparticles containing α-fetoprotein siRNA induce apoptosis and enhance the cytotoxic effects of doxorubicin in human liver cancer cell line - Theeraphong Pho-iam (2022)
Hepatocellular carcinoma (HCC) is one of the most common cancers and is a leading cause of death. Delivery of therapeutic molecules, e.g., siRNA, to HCC cells could potentially be an alternative treatment for HCC. In this study, the siRNA targeting α-fetoprotein (AFP) mRNA was found to specifically induce apoptosis and significant cell death in HepG2 cells. It also enhanced the cytotoxic effects of doxorubicin by about two-fold, making it the candidate therapeutic molecule for HCC treatment. To deliver the siRNAs into HCC cells, the AFP siRNAs were loaded into the nanoparticles based on poly (lactic-co-glycolic) acid (PLGA). These nanoparticles induced apoptosis in HepG2 cells and synergistically increased the cytotoxicity of doxorubicin. In summary, the delivery of the AFP siRNA-loaded PLGA nanoparticles in combination with doxorubicin could be a very promising approach for the treatment of HCC.